ANALISIS KUAT TEKAN BETON DENGAN BAHAN TAMBAH REDUCED WATER DAN ACCELERATED ADMIXTURE - Rahmat Rahmat; Irna Hendriyani; Moh. Syaiful Anwar (Universitas Lambung Mangkurat, 2016)
Concrete consist of: cement mortar, coarse aggregate, fine aggregate, water, and addictive materials. The main ingredient in manufacturing of concrete: rock material that called as aggregates. Aggregate has an important role on the quality of the concrete. Various types and trademarks for admixture of concrete that can be used as addictive of the concrete mix with specific purpose. The study aims to determine the effect of the added material of Reduced Water and Accelerated Admixture (Bestmittel) on compressive strength of concrete.The research was conducted in four variations with compressive strength of 25 MPa. One of each variation consists of nine cylinders with length of 30 cm and diameter of 15 cm. Concrete mix with added material Reduced Water and Accelerated Admixture (Bestmittel) in testing at the age of 7 days, 14 days and 28 days, with a variation of 0.2%, 0.4% and 0.6% with 9 samples one of each them. One is normal concrete cylindrical specimen as comparison.The research show by adding Reduced Water and Accelerated Admixture (Bestmittel) by 0.2%, 0.4% and 0.6% by weight of cement and water will (1) increase the workability and (2) increase of average compressive strength of normal concrete (0,2% for 25.61 Mpa; 0,4% for 27.66 Mpa; 0,4% for 29.50 Mpa; and 0,6% for 31.44 Mpa).